Proof positive - Mayor, Archer (Mayor, Archer. Joe Gunther novel., 2014)
Investigating the death of a Vietnam veteran whose PTSD culminated in a hoarding disorder, Joe Gunther learns that the victim's collection of combat photos contains information that a sinister adversary desperately wanted to keep hidden.